REKONSTRUKSI HUKUM KELUARGA MELALUI PENDIDIKAN PRA-NIKAH: ANALISIS PERBANDINGAN KERANGKA HUKUM INDONESIA DAN MALAYSIA - Aripin, Jaenal; Hakim, Maman Rahman; Kamarusdiana, Kamarusdiana; Ilahi, M. Ridho (Jurnal Harkat : Media Komunikasi Gender, 2025)
Abstract. The regulation of premarital education in Indonesia has not succeeded in reducing the divorce rate in Indonesia. Weak regulations, unclear standardization, and the nature of the program that is recommended and only required in 2024 which tends to be formalistic are the main factors. This study aims to analyze the regulation of pre-marital education and its effect on divorce in Indonesia and Malaysia. The researcher used a qualitative method by reviewing various literatures and data obtained from journal articles, books, and news. The results show the need to reconstruct the law to tighten the provisions, centralize management at the Ministry of Religious Affairs through BP4, and make premarital education a mandatory requirement that is not just a formalistic implementation. Malaysia's experience, which has successfully reduced the divorce rate, can be emulated even though it is still constrained in its implementation, which needs to be addressed by conducting socialization related to the importance of the program, evaluating the duration of the program, and evaluating the resource persons or presenters. Thus, future Indonesian and Malaysian pre-marital education regulations are expected to be able to prepare couples to form a socially, emotionally and spiritually healthy family to prevent long-term social dysfunction, one of which is divorce. Abstrak. Regulasi pendidikan pranikah belum berhasil menekan angka perceraian di Indonesia. Lemahnya regulasi, ketidakjelasan standarisasi, serta program yang bersifat anjuran dan baru diwajibkan pada 2024 yang cenderung formalistik menjadi faktor utama. Penelitian ini bertujuan untuk melakukan analisis terhadap regulasi mengenai pendidikan pra nikah dan pengaruhnya terhadap perceraian di Indonesia dan Malaysia. Peneliti menggunakan metode kualitatif dengan wawancara dan mengkaji berbagai literatur serta data yang diperoleh dari artikel jurnal, buku, berita, dan data statistik. Hasil penelitian menunjukkan perlunya melakukan rekonstruksi ke tingkat undang-undang guna memperketat ketentuan, memusatkan pengelolaan pada Kementrian Agama Melalui BP4, serta menjadikan pendidikan pranikah sebagai syarat wajib yang tidak hanya sekedar pelaksanaan yang formalistik. Pengalaman Malaysia, yang sukses menekan angka perceraian dapat dicontoh meski masih terkendala dalam implementasinya yang perlu untuk dibenahi dengan melakukan sosialisasi terkait pentingnya program, evaluasi durasi program, serta evaluasi bagi para narasumber atau pemateri. Dengan demikian regulasi pendidikan pra nikah Indonesia dan Malaysia di masa mendatang diharapkan mampu menyiapkan pasangan yang sehat secara sosial, emosional, dan spiritual untuk mencegah disfungsi sosial jangka panjang yang salah satunya adalah perceraian.